PENGARUH GENDER TERHADAP PERBEDAAN SPESIFIC VALUES PADA MAHASISWA AKUNTANSI - Purnamasari, Dian Indri (Universitas Muhammadiyah Surakarta, 2008)
The problems concerning to the ethics in auditing profession is closely related to the values of the individuals involving in the profession. The study aimsat finding empirical evidences whether there is the difference in the specific values of the female and male students of accounting. The results of the analysisof independent sample t-test indicate that there is the difference in specific values between the female and male students of accounting. In other words, the gender gives impact to the difference in the specific values of the male students of accounting. Further analysis indicates that in fact the difference in the specificvalues is caused by the presence of the impact of gender on the aesthetic values, while individual, social and theoretical values between the female and male students of accounting are the same or do not have any impact on the individual,social and theoretical values.